CXC leaders and pioneers : speech delived at CXC 40th Anniversary Evening of Elegance held at the Jamaica Pegasus Hotel on 25 October 2013 - Walter, Irene (2013)
Posits that the successes achieved by CXC has been possible due to the exceptional leadership roles proivided by all CXC chairmen.